Application of a modified clinical classification for pulmonary arterial hypertension associated with congenital heart disease in children: emphasis on atrial septal defects and transposition of the great arteries. An analysis from the TOPP registry - Wacker, Julie; Humpl, Tilman; Berger, Rolf M. F.; Ivy, Dunbar; Bowers, David; Bonnet, Damien; Beghetti, Maurice (Frontiers in Cardiovascular Medicine, 2024)
Disclosures: Actelion does not participate in the management of the TOPP registry; neither does it have access to the database and the individual site and patient data. All decisions related to the Registry lie solely with the Executive Board of the Association for Pediatric Pulmonary Hypertension. The M3C-Necker contracts with Actelion, Bayer, Novartis, MSD and Lilly for Dr. Bonnet to perform consultant activities and to participate in steering committees for clinical trials. Dr. Beghetti has received grants from and contracted as consultant for Actelion and Bayer-Schering; and served as a consultant and participated in the steering committee for Actelion